URGENSI KEBIJAKAN HUKUM PENATAAN RUANG PROVINSI KEPULAUAN DALAM SISTEM PENATAAN RUANG NASIONAL - Zainuri, Zainuri (DiH: Jurnal Ilmu Hukum, 2018)
Article 25 A of the 1945 Constitution of the Republic of Indonesia states that the Unitary State of the Republic of Indonesia is an archipelagic State characterized by the archipelago with its territories and boundaries and rights established by law. In addition to the archipelago of Indonesia is also called coastal state (coastal state) whose national territorial components consist of land, sea, and air space, where two thirds of the total territory of Indonesia is in the form of oceans. In the year 2007 Indonesia has established a legal regulation relating to spatial planning system that is Law Number 26 Year 2007 on Spatial Planning. However, Law Number 26 Year 2007 discusses a very big problem with respect to the national spatial system. In Law Number 26 of 2007 does not specifically regulate the area that characterize the archipelago. In the case of Article 3 of Law Number 26 Year 2007 regarding spatial arrangement stipulates the Implementation of spatial planning aims to create a safe, comfortable, productive and sustainable national territory based on Nusantara Insight and National Resilience. Based on the background of the problem the authors take the legal issue of "What is the Urgency Policy of Spatial Planning Provincial Islands System of National Spatial Planning System". In this writing the author uses a normative juridical approach. Island archipelagic spatial planning policy which is not the same as spatial space in Law Number 26 Year 2007 on Spatial Planning which is based or land-oriented but more in favor of middle to lower society because majority of society in The archipelagic region is the middle and lower society, especially fishermen, fish traders, farmers and others, so it needs a favorable spatial planning policy for the people who are in the archipelago, the presence of the state is necessary to protect and protect the island community of course the presence of the country is not only for a moment but that presence is something sustainable.